A systematic review and meta-analysis of antibiotic-impregnated bone cement use in primary total hip or knee arthroplasty. - Jiaxing Wang; Chen Zhu; Tao Cheng; Xiaochun Peng; Wen Zhang; Hui Qin; Xianlong Zhang (PLoS ONE, 2013)
Background Antibiotic-impregnated bone cement (AIBC) has been widely used for the treatment of infected revision arthroplasty, but its routine use in primary total joint arthroplasty (TJA) remains considerably controversial. With this meta-analysis of published randomized controlled trials, we intended to assess the antimicrobial efficacy and safety of AIBC for its prophylactic use in primary TJA. Methods A literature search was performed in MEDLINE, Embase, CBMdisc and the Cochrane Library until June, 2013. The studies were divided into two sub-groups according to the type of the control group. Outcomes of interest included postoperative infection rates, radiographic outcomes and clinical joint score. Study quality was evaluated using the Jadad scale (five points). Results In total, eight studies were included, with a sample size of 6,381 arthroplasties. The overall pooled data demonstrated that, compared with the control (plain cement or systemic antibiotic), AIBC did not reveal an advantage in decreasing the rate of superficial infection (relative risk [RR] = 1.47; 95% CI, 1.13-1.91; P=0.004), while there were significant differences in deep infection rate between the AIBC and control group (RR = 0.41; 95% CI, 0.17-0.97; P=0.04). For the analysis of gentamicin and cefuroxime subgroups, the gentamicin was superior to the cefuroxime in reducing deep infection rate (P=0.0005 versus P= 0.10). However, no significant differences were found in their radiographic outcomes and clinical joint score. Conclusion This meta-analysis had proven that the prophylactic use of AIBC could lower the deep infection rate in primary TJA, while AIBC did not show an improvement in reducing the superficial infection rate compared with the control. More sufficiently powered studies would be required to further evaluate the efficacy and safety of AIBC for primary TJA.